Intracellular drug delivery by genetically engineered high-density lipoprotein nanoparticles. (August 2010) - Murakami, Tatsuya; Wijagkanalan, Wassana; Hashida, Mitsuru; Tsuchida, Kunihiro
Aim: Nascent high-density lipoprotein (HDL) capable of intracellularly delivering anticancer drugs was developed to potentiate antitumor activities.Materials & methods: Apolipoprotein A-I, a major component protein of HDL, was genetically fused to TAT peptide, a protein transduction domain. Nascent HDL was prepared with this mutant and phospholipids. Results & discussion: Intracellular delivery of doxorubicin (DXR) by TAT-fused HDL was confirmed by confocal microscopy. Treatment of cancer cells with TAT-fused HDL–DXR complex resulted in enhanced growth inhibition. Furthermore, TAT-fused HDL–DXR complex suppressed tumor growth in mice more efficiently than HDL–DXR complex. No bodyweight loss was observed for the TAT complex. These results clearly demonstrate the usefulness of TAT fusion to nascent HDL to potentiate the antitumor activity of DXR.Conclusion: The genetic fusion of apoA-I with biologically active peptides potentially enables a simple assembly of biocompatible and versatile drug carriers.